DESIGN OF BUSINESS MODEL INNOVATION FOR POWER PLANT OPERATION AND MAINTENANCE SERVICES USING DESIGN THINKING METHOD - Putri, Nikita Ashardika; Nadlifatin, Reny (Jurnal Bisnis dan Keuangan, 2023)
Power generation business competition in Indonesia is increasingly competitive due to the growth of IPP’s with better levels of reliability and efficiency. IPP growth with the TOP scheme in PJBTL has the potential to burden PLN and the state's finances in the long term. In order to guarantee the sustainability of the company, this needs to be a concern of PLN and its subsidiary, PLN Nusantara Power (PLN NP). PLN NP is expected to be able to provide more competitive O&M service fees. This study aims to formulate cost efficiency O&M services based on factors that affect the cost of supplying electricity, to provide efficient and competitive O&M service costs. The research began with the in-depth interviews with experts and reports of electricity supply, O&M service business processes, list of power plant units which were analyzed using the design thinking method, and supported by the cost leadership and blue ocean strategy. The results of the analysis obtained from this study have been validated by experts, in the form of proposed formulations that are studied comprehensively, and are able to solve O&M service cost problems by implementing a cost leadership strategy through changes to return on investment schemes, use of local workforce, appointment schemes directly, as well as the transfer of 3rd party contracts. This research proves that the proposed formulation is able to support O&M service cost efficiency of 9.5%.